Doing more, feeling better: A behavioural approach to helping a woman overcome low mood and anxiety. (23rd July 2014) - Stuart, Simon; Graham, Christopher D.; Butler, Sarah
<x xml:space="preserve">Abstract</x> Accessible summary Much has been written about how best to help people with learning disabilities if they feel sad or worried. Often this is about thinking. But it might be better to look at doing instead. This is the story of how we tried to help a lady feel happier, and worry less. Summary A substantial body of literature exists concerning the adaptation of Cognitive Behavioural Therapy for people with learning disabilities. However, it is possible that cognitive approaches have been prioritised at the expense of behavioural techniques that are simpler and more effective. This case conceptualisation considers a behaviourally focused approach to helping a woman with a mild learning disability who was experiencing low mood and anxiety, delivered by a trainee clinical psychologist working within a multidisciplinary team.